The Influence of Intellectual Intelligence and Emotional Intelligence on Accounting Understanding among Accounting Students of the Institut Teknologi dan Bisnis Master Pekanbaru - Sari, Hernita (Reflection: Education and Pedagogical Insights, 2024)
This research aims to examine the influence of intellectual intelligence and emotional intelligence on understanding accounting among accounting students at the Pekanbaru Master's Institute of Technology and Business. The variables that researchers use is Intellectual Intelligence (X1), Emotional Intelligence (X2) and Accounting Understanding (Y). The data source in this research is primary data where the data collection method uses a questionnaire. The number of samples in this research was 52 samples using the survey method. The analytical method in this research uses multiple linear regression analysis using SPSS. The results of this research show that Intellectual Intelligence has no effect on understanding accounting, Emotional Intelligence has a significant effect on understanding accounting, intellectual intelligence and emotional intelligence simultaneously have a significant effect on understanding accounting.